PENGARUH MODEL PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS III SEKOLAH DASAR - Ripena, Ripena; Salimi, Asmayani; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn learning to write poetry in class III of Public Elementary School 09 Southeast Pontianak, students 'understanding of learning material was not maximized, thus influencing students' writing skills especially in poetry writing skills. In addition, the lack of training in poetry writing results in low skills and student learning outcomes in Indonesian subjects so that it requires an innovative and fun learning model. One of the learning models that have been proven to support students' skills in writing poetry is to use the picture and picture model. The problem in this study is "Are Picture and Picture Models Influencing Poetry Writing Skills of Students in Class III of Public Elementary Schools 09 Southeast Pontianak?" The research method used is the Experimental method, while the research form used is one group test and post-test. The sample in this study is 19 third grade students. Data collection techniques used in this study are direct observation techniques and techniques measurement. Based on the results of data analysis, the mean score of the pre-test was 63,3157 and the average post-test was 72,1052. The results of the t test obtained by the table are significantly different = 5% is 1,734. Because thitung (14,5714)> t table (1,734), then testing the hypothesis of the post-test data is accepted. From the effect size (ES) calculation, ES is obtained for 1.27 including high category, this means that the use of the picture and picture model influences the poetry writing skills of third class students of Elementary School 09 Southeast Pontianak.Â Keywords: The effect, Picture and Picture, Poetry writing skills